Country report. Hong Kong, Macau - Economist Intelligence Unit (London Economist Intelligence Unit, 2009)
Each Country Report contains in-depth and ongoing analysis and forecasts of political, policy and economic conditions to help you understand what is happening now and to gain a picture of how Hong Kong will look in the future
The library has one issue only (Dec 2009)
Keywords: Economic conditions; ECONOMIC CONDITIONS; POLITICAL CONDITIONS; ECONOMIC POLICY; HONG KONG; MACAU; PERIODICALS